Water-responsive supercontractile polymer films for biomedical applications - Yi, Junqi (Nanyang Technological University, 2022)
Stimulus-responsive contractile materials are significant both in nature and in our daily lives. Contraction of muscles is the basis of animal movement. Supercontraction of spider dragline silks is related to their superior mechanical properties. The synthetic heat shrink polymers are widely used in packaging. All these natural and commercial contractile materials exhibit large (~ 50%) and fast (within seconds) contraction, a prerequisite of their functioning. Advanced stimulus-responsive contractile materials with different stimulus like heat, light and chemicals have been developed recently. But only a few of them achieve fast and large contraction. Besides, in terms of biomedical applications, stimulus like high temperature, ultraviolet light and harmful chemicals are incompatible with vulnerable physiological environment. Body-temperature (37 °C) are suitable stimulus, but this low transition temperature increases the premature contraction risk at ambient conditions. Water is also a benign stimulus. But most of the water-responsive contractile materials are based on water-breakable hydrogen bonds as switch segments, overly dense of which hinder contraction while sparse ones are unstable under ambient humidity. This thesis designs a series water-responsive supercontractile films. These films are stable at ambient environmental conditions and exhibit large and fast contraction when wetted. Based on them, this thesis develops two new biomedical devices: shape-adaptive electronic-tissue interfaces and automatic wound closure tapes.